(untitled) (Sains Humanika, 2021)
Indonesia has a variety of cultures in each region. Javanese culture in general namely konco wingking and the Banyumas culture which is one of the parts of Java, namely cablaka, it contributes to the development of women careers because there are contradictions between the two cultures. This systematic review aims to examine the fear of success in women working with the Banyumas cultural approach. The inclusion and exclusion criteria like data that used in 2009-2019 time frame, data obtained from the site https://scholar.google.co.id, the data that used is related to fear of success, cablaka, and Javanese women. Based on the results of the literature review, it is understood that fear of success is an obstacle to women career development because of the fear of negative results obtained (loss of femininity, loss of social self-esteem, and loss of social rejection). Women who experience fear of success blame the culture as a set of internal hope. Javanese women has culture, the name is konco wingking. It is a caste differentiate between women and men, where men have a higher position. Cablaka culture is a culture of the spontaneity of the Banyumas community towards everything that happens in plain sight without being covered up. The orientation of Banyumas cultural values shows that there are five Banyumas human relations with the meaning of life, work, time, nature, and fellow humans.